Failed diplomacy the tragic story of how North Korea got the bomb - Pritchard, Charles L. (Brookings Institution Press, 2007)
"Offers an insider's analysis of developments on the Korean peninsula and how North Korea was able to develop nuclear weapons. Provides a first-hand account of how the Six-Party Talks were initiated, with a step-by-step review of each round of negotiations, detailing the national interests of the key players"--Provided by publisher.